A Multi‐Layer Stacked Triboelectric Nanogenerator Based on a Rotation‐to‐Translation Mechanism for Fluid Energy Harvesting and Environmental Protection. (13th December 2022) - Zhou, Hanlin; Wei, Xuelian; Wang, Baocheng; Zhang, Enyang; Wu, Zhiyi; Wang, Zhong Lin
Abstract: Energy shortage and environmental degradation are two important challenges facing humanity. Here, a multi‐layer stacked triboelectric nanogenerator (MLS‐TENG) based on a rotation‐to‐translation mechanism is reported for fluid energy harvesting and environmental protection. The mechanism transforms fluid‐induced rotation into a reciprocal translation of the MLS‐TENG, enabling the conversion of fluid energy into electrical energy. In addition, benefiting from a multi‐layer stacked structural design, the open‐circuit voltage is increased from 860 to 2410 V and an efficient energy harvesting rate of 2 mJ min −1 is obtained in an actual river. Furthermore, with the assistance of the MLS‐TENG, a self‐powered wireless temperature and humidity monitoring system and a metal anticorrosion system are successfully established. Ambient monitoring data can be transmitted continuously at an interval of 49.7 s, and the corrosion rate of steel is significantly slowed down. This study provides guidance for efficient harvesting of ambient fluid energy, with promising applications in environmental monitoring and protection. Abstract : A multi‐layer stacked triboelectric nanogenerator based on a rotation‐to‐translation mechanism (MLS‐TENG) is presented here. The stacked multi‐layer structure enables a stable increase in the electrical output of the device, and the MLS‐TENG‐based self‐driven wireless environmental monitoring and metal anticorrosion system demonstrates its applications potential for environmental protection.